Business Process Management for Increase Efficiency Process on Leads Generation Acquisition in Saas Company (a Case Study Approach) - Dyan Rachmatullah; Sfenrianto Sfenrianto (Departement of Mathematics Education, 2023)
Customer acquisition is the backbone in the growth and development of a company, especially for startups. Companies can build business processes to create opportunities for potential prospects who can convert into new customers who gain trust and are ready to make a purchase. However, in this process various obstacles were encountered, such as the ineffective process of managing prospective customer data, the level of accuracy and validity of data to the low conversion rate of data from prospective users to become new customers. This research was conducted by a startup company in Indonesia engaged in the Software as Services (SaaS) industry. The approach used in the above problems is business process management (BPM) which is able to re-design and abstract the currently running processes to produce more efficient and logical business processes. This BPM approach is carried out with a business process management lifecycle framework that is capable of structuring and standardizing processes into processes of identification, discovery, analysis, redesign, implementation, monitoring and controlling. This study provides an overview and recommendations of companies that are arranged systematically starting from the findings of both quantitative and qualitative data, then analyzing the process, establishing a new, more efficient business model to measuring post-implementation impacts. The use of the BPM lifecycle method is intended to improve data accuracy, speed up the process of managing prospective customer data so that in the end it is able to contribute and increase company revenue.